Fabrication of a one-dimensional tube-in-tube polypyrrole/tin oxide structure for highly sensitive DMMP sensor applications. Issue 33 (3rd August 2017) - Jun, Jaemoon; Lee, Jun Seop; Shin, Dong Hoon; Oh, Jungkyun; Kim, Wooyoung; Na, Wonjoo; Jang, Jyongsik
Abstract : 1D tube-in-tube polypyrrole/tin oxide structure was fabricated using electrospinning and vapor deposition polymerization to construct the DMMP gas sensor, which shows high sensitivity and selectivity. Abstract : Detection of toxic gases is of great importance for protection against chemical weapons. In particular, organophosphates, such as sarin, damage nerve function and are fatal inhibitors of acetylcholinesterase. Therefore, simple and enhanced technologies for the detection of organophosphates are needed. Herein, we report the fabrication of a chemiresistive gas sensor based on a polypyrrole (PPy)-coated SnO2 tube-in-tube structure that was highly sensitive (0.05 ppb) and selective toward dimethyl methylphosphonate (DMMP), which is a simulant of organophosphates. The complex tube-in-tube structure was fabricated using a single-nozzle electrospinning method with two mixed solvents. Vapor deposition polymerization (VDP) was used to form a thin PPy layer on the surface of the SnO2 tube-in-tube structure without any aggregation. Our new synthetic methodology promises to be an effective approach for fabricating organic/inorganic complex tubular structures for future sensing technologies.